Automated organizations : Development and structure of the modern business firm - Oliveira, Nelio (Contributions to Management Science, 2012)
This book attempts to characterize a new organizational form that is now visible in many companies as a substitute of previous forms related to mechanized or mechanistic standards. The book is based on the approach of organizational structure and on Henry Mintzberg's work on organizational configurations. As a matter of fact, it attempts to supplement and update Mintzberg's organizational taxonomy, taking into account changes in the structure and work organization of business firms. The book is written for all people whose work is related to organizations and who are interested in the subjects it deals with.